Pengaruh Capital Adequacy Ratio, Biaya Operasional terhadap Pendapatan Operasional, Loan to Deposit Rasio, dan Non-Performing Loan Terhadap Kinerja Keuangan - A. Isramiarsyh; Mursalim Nohong; Andi Aswan (Hasanuddin Journal of Business Strategy, 2019)
This research aims to (1) analyse the influence of Capital Adequacy Ratio (CAR) against the financial performance and the value of the company. (2) analyse the influence of operational costs against operating income (BOPO) against the financial performance and the value of the company. (3) Analyze the influence of the Loan to deposit ratio (LDR) towards the financial performance and the value of the company. (4) analyze the effect of Non Performing Loan (NPL) against the financial performance and the value of the company, as well as analyse the influence of the financial performance of the company. The type of research used in this research is quantitative research. The population in this research is the banking industry companies listed on the Indonesia stock exchange. The technique used is the sample determination of purposive sampling. Data analysis techniques used are qualitative analysis, test the assumptions of classical, path analysis (Path analysis) as well as testing the hypothesis. The results of research that the capital adequacy ratio (CAR) was not significant and positive effect on performance of Finance (ROA), where the higher capital adequacy ratio then the profit achieved increases. While the capital adequacy ratio is a positive and significant effect against the value of the company, because of the higher capital requirement then the value of the company increases. The ratio of Loan to Deposit Ratio (LDR) of influential positive and not significantly to financial performance (ROA), where the higher the kiredit transmitted then the profits achieved by the company will increase. Similarly, a positive and influential LDR significantly to the value of the company, because the higher the credit is tersalurkan then the interest income will increase. The ratio of Non Performing Loan (NPL) negative effect on performance of Finance (ROA), where the higher the handling of bad debt (doubtful, less smoothly and crashes) then the profit achieved would plummet. While a negative and significant effect the NPL against values of company, because the higher bad debt then will lower the value of the company and this would affect investor companies to embed its stake in banking.